The Love of Emma Goldman Against the Great War (1917): New Readings from the History of Emotions - Peña Castillo, Francisco Javier (Revista de Historia Social y de las Mentalidades, 2024)
This article examines the potential insights that the history of emotions can provide for studying the anarchist movement, particularly its internal tensions. It focuses on the various expressions of love demonstrated by Emma Goldman during her 1917 trial, where she faced accusations of conspiring against the conscription imposed by the United States government during the Great War. The goal is to explore her political project's central and multifaceted aspects. Utilizing various sources, her autobiography serves as a key experiential testimony. The article addresses what has been previously said about love within anarchism and, more importantly, how it was experienced.
Keywords: Free Love; History of Emotions; Emotional Communities; Emotional Regime